Analysis of fig tree virus type and distribution in China - Mahmut Mijit (Journal of Integrative Agriculture, 2017)
The common fig (Ficus carica L.) was one of the earliest horticultural crops to be domesticated. A number of different viruses can infect fig trees including Fig mosaic virus (FMV) that has been detected in several commercial fig trees in Xinjiang, China. However, the distribution of FMV and other fig-infecting viruses in China remains unknown. In the present study, a sample from an ancient fig tree growing in Xinjiang was investigated by electron microscopy (EM) followed by PCR/RT-PCR, and FMV, Fig badnavirus 1 (FBV-1) and Fig leaf mottle-associated virus 1 (FLMaV-1) were detected. Fig leaf samples (252) from commercial orchards across China were subjected to PCR/RT-PCR, and FMV, FBV-1 and Fig fleck-associated virus (FFkaV) were relatively abundant (44.4, 48.4 and 44%, respectively), while FLMaV-1 and Fig mild mottle-associated virus (FMMaV) were much scarcer (5.6 and 0.4%, respectively), and FLMaV-2, Fig cryptic virus (FCV), and Fig latent virus (FLV) were not detected. The presence of disease-causing viruses in fig trees presents a significant challenge for fig producers in China. This study may help to promote actions aimed at controlling fig viruses, especially FMV.